Analisa Prediksi Penjualan Jersey World Cup 2018 Terlaris Dengan Menggunakan Metode Support Vector Machine (Studi Kasus: Toko One Sport Football Distro) - Ahmad Suhairy Batubara (Journal of Information System Research (JOSH), 2020)
Jersey has become a new outbreak that has blended among the people of Indonesia, no longer used by men even the jersey has been used by women. No wonder that jersey is often found in places that have nothing to do with football, such as: campuses, public roads, malls, and banks in enlivening certain events. With so much community interest in jersey, the jersey shop owner has the opportunity to earn huge profits. Moreover, the world cup which is held every 4 years makes the euphoria of the people become big. But in fact there is still often a shortage of stock which causes the store to waste the opportunity that exists from an event or an excess stock of goods that will make the store suffer losses due to unsold goods. Prediction is done to estimate the value for the future to take a decision. This study uses the support vector machine method is expected to be able to predict sales of 2018 world cup jersey. By using the polynominal kernel function to get a predictive value, and the results concluded are the support vector machine method is able to predict sales of 2018 world cup jersey.